BUSINESS INTELLIGENCE IN THE PROCESS OF DECISION MAKING: CHANGES AND TRENDS - Vizgaitytė, Gintarė; Rimvydas, Skyrius. (Ekonomika, 2012)
The concept of business intelligence has drawn substantial attention of both academicians and practitioners. As one of the fastest eveloping business application areas, business intelligence has also created a trail of confusion regarding its role, potential, sources of value creation. This study aimed at elucidating the role of business intelligence in the near future through the analysis of the current research and practical trends. The current prevailing trends in business intelligence technologies and systems are mobile business intelligence, location intelligence, software as a service, big data and predictive analytics. The paper points out that human factors in business intelligence are often underestimated, while a thorough consideration of their role should create additional ground for effective business intelligence applications. Some of the important considerations regarding human factors, such as support of problem-solving patterns and an efficient coordination of business intelligence activities, are presented.